Hubungan antara konsep diri dan kemampuan verbal dengan prestasi belajar pada siswa kelas lima Sekolah Dasar Muhammadiyah Sukonandi Yogyakarta - Kusno Efendi (HUMANITAS: Indonesian Psychological Journal, 2004)
The main objectives of the present research were to (1) understand the correlation between self-concept and verbal ability with learning achievement, (2) understand the difference of self-concept and verbal ability between boys and girls.The population of this research were 2 Muhammadiyah Elementary Schools of 8 whose classification are good (A). Two out of the Muhammadiyah Elementary Schools was used as the population of this study. Subjects of the study were 79 students of grade 5 students Muhammadihah Sukonandi and Karangkajen Elementary Schools. The subjects consisted of 42 boys and 37 girls who ages were between 9 to 13.The data of self-concept were collected using questionnaire, consists of 32 items. The verbal ability data were collected using WISC Verbal Test. Documentation is the instrument used to find achievement data.The result of analysis data showed that: (1) The correlation between self-concept and verbal ability with learning achievement were significant, R = 0.520 p = 0.000 < 0.025. (2) There was no difference of self-concept between biys and girls, t = 0.796, p = 0.566 > 0.025.